Impacto del entrenamiento visual deportivo en el fútbol y en el béisbol (2022)
Visual sports training is a personalized program that, through exercises and a multidisciplinary group, seeks to enhance cognitive and motor skills. Physiological bases, experience and technology have been key to determining a guide that empowers the athlete and takes him to another level.